1995
DOI: 10.1111/j.1476-5381.1995.tb13286.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of muscarinic M2 receptors after the early allergic reaction: possible contribution to bronchial hyperresponsiveness in allergic guinea‐pigs

Abstract: 1. Using a guinea-pig model of allergic asthma, in which the animals display early (0-5 h) and late phase (8-23 h after antigen challenge) bronchoconstrictor reactions, the function of prejunctional inhibitory M2 and postjunctional M3 receptors in isolated tracheal preparations have been investigated. In addition, cardiac M2 receptor function in vitro and bronchial responsiveness to histamine in vivo were evaluated. 2. Sensitivity to inhaled histamine was increased 3.1 fold and 1.6 fold after the early and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 33 publications
2
14
1
1
Order By: Relevance
“…Therefore, the dysfunction of M 2 muscarinic autoreceptors might increase vagally-mediated airway contraction. Furthermore, histamine-induced airway contractions may be caused by a decrease in M 2 muscarinic autoreceptors [29]. Therefore, increased airway response to histamine in BHS [2,[22][23][24] may also be due to the dysfunction of M 2 muscarinic autoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dysfunction of M 2 muscarinic autoreceptors might increase vagally-mediated airway contraction. Furthermore, histamine-induced airway contractions may be caused by a decrease in M 2 muscarinic autoreceptors [29]. Therefore, increased airway response to histamine in BHS [2,[22][23][24] may also be due to the dysfunction of M 2 muscarinic autoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have subsequently been confirmed in other experiments using diVerent models of antigen challenge. [39][40][41][42] Increased concentrations of acetylcholine have been reported in the airways of other antigen challenged animals including mice, 43 dogs, 44 and guinea pigs, 43 providing indirect supportive evidence that there is loss of function of neuronal M 2 muscarinic receptors in the airways of animal models of hyperreactivity.…”
Section: -35mentioning
confidence: 99%
“…In addition, although not synergistic, it was found that olodaterol, tiotropium, and their combination fully inhibited the AHR after the LAR. The cause of the lack of synergism in protecting against the AHR after the LAR is unknown, but could well be related to a relatively lower cholinergic tone after the LAR than after the EAR (Ten Berge et al, 1995), thereby not exposing a potential synergism. Nevertheless, from a clinical perspective, the protection against the AHR after the LAR by both olodaterol and tiotropium, as well as their combination, is of importance.…”
Section: Synergism Between Olodaterol and Tiotropiummentioning
confidence: 99%